SPECTRAL, STRUCTURAL AND THERMAL STUDIES OF THE DIVALENT METAL ION COMPLEXES OF PHENYLHYDRAZOETHYLACETOACETATE HYDRAZONE - Kashar, T.I. (European Scientific Journal, ESJ, 2013)
Metal complexes of phenylhydrazoethylacetoacetate hydrazone derived from phenylhydrazoethyl acetoacetate and thiosemicarbazied (HL) are reported and characterized based on elemental analyses ,IR , electronic spectra, magnetic moment , molar conductance, ESR and thermal analyses . The molar conductance data reveal that the complexes are non-electrolytes while Mn(II) complex is electrolytes.IR spectra show that the ligand (HL) coordinated to the metal ions in a tridentate manner with ONS doner sites . TGA and DTA showed that the complexes are thermally stable. The data of thermal analyses and the calculated activation kinetic parameters of the decomposition of the prepared complexes show that the thermal stability of metal complexes depends essentially on the nature of both the central metal ion and the ligand.